Goitre: An Iodine Deficiency Disorder - Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
Goitre is one of the well known manifestations of iodine deficiency disorder. It can be prevented by consuming iodized salt to remove iodine deficiency.